PELAKSANAAN METODE APPLIED BEHAVIOR ANALYS DALAM PENINGKATAN KEMAMPUAN KOMUNIKASI RESEPTIF ANAK AUTIS DI LEMBAGA TERAPI - Sedya Silo Pratiwi, Tri (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: Applied Behavior Analys is a structured, purposeful and clear method. Autistic child receptive communication there are two types, the ability to listen and read. Communication barriers experienced by children with autism is communication listening and reading include the ability to understand the message conveyed by others, in addition to the ability of receptive communication includes the ability to communicate with others. Research method in this research is using qualitative approach descriptive type. The location of the research was at Little Star Gresik Therapy Institute using Applied Behavior Analys method in the learning process. The purpose of this study describes the implementation of Applied Behavior Analys method in improving the receptive communication of children with autism in the Institute of Therapeutic Little Star Gresik. Data collection techniques with observation in the therapy room, interviews and documentation studies. While the data analysis techniques using data reduction (data reduction), display data (presentation data), and conclution drawing / verification (withdrawal and verification). The implementation of Applied Behavior Analys method in Autistic children who experience receptive communication barrier at Therapeutic Institute of Little Star Gresik faces obstacles to the implementation aspect of principle and technique, because the implementation of Applied Behavior Analys which requires the child to follow the instruction of the teacher so that the child feel saturated in the learning process takes place. Therapists or teachers provide a solution for parents to always monitor child development and modify so that children do not get bored and saturated during the learning process takes place. Keywords: Applied Behavior Analys method, Communication Barriers, Receptive Communication